The efficient urban governance in managing and enhancing competitiveness of property markets in Kuala Lumpur city-region - Azmizam Abdul Rashid ,; Hamzah Jusoh ,; Habibah Ahmad, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
This article discusses on the preliminary study of efficient urban governance (EUG) towards enhancing competitiveness of the property market with regards to the performances of the shopping complexes and office sectors in the Kuala Lumpur city-region (KLCR). City-region competitiveness is currently one of the major tasks in the country’s development agenda. The issue is more obvious when the city-region acts as an engine of growth to help attaining a fully developed nation by 2020. Bearing in mind that the urban governance is one of the key players to spearhead the city region economy and the property market in particular, the roles of urban governance in managing and enhancing the competitiveness of property markets is crucial. Nevertheless how well does the urban governance enhance the efficiency of local authorities (LAs) in city-region is understudied. Another aspect is the extent of the EUG initiaties to boost the property market within city-region. Based on a study carried out in 2009 and the Kuala Lumpur City Plan 2020, and the National Property Information Centre (NAPIC) 2009 act as the basis of discussion., this article discusses the performances of the property market in city-region economy. The study found that the main challenge of enhancing competitiveness of property sector in city-region is the implementation of efficient urban governance by LAs. One crucial prequisite is the existence of urban governance that integrates all sectors including public, private and other social organisations in participatory decision making. In particular, EUG helps to speadhead the city region and property market as the principles of sustainability, subsidiarity, equity, transparency and accountability, civic engagement and citizenship and security are secured and in practiced.